Cara Praktis Menulis Buku: Panduan mudah yang akan membantu anda dalam menulis buku - An Nuur Budi Utama (Deepublish, 2014)
Cara Praktis Menulis Buku: Panduan mudah yang akan membantu anda dalam menulis buku